Macrophage heterogeneity in liver fibrosis - Wang, Wenzhao; Li, Shengwen; Liu, Yanjun; Ding, Xin; Yang, Yongqi; Chen, Shiyun; Cao, Jiafan; Tacke, Frank; Dong, Wei; Lan, Tian (Frontiers in Immunology, 2025)
Liver fibrosis represents a universal pathological endpoint in chronic hepatic disorders, in which hepatic macrophages play a pivotal role through dynamic phenotypic modulation. These versatile immune cells undergo functional and phenotypic transformations mediated by diverse molecular mediators, with their heterogeneity arising from both cellular origin differences and disease-specific microenvironments. The development of technologies such as single-cell and spatial omics has broken through the traditional M1/M2 classification paradigm of macrophages, revealing the molecular signatures and functional distinctions of hepatic macrophages during liver injury, fibrogenesis, and regression. Hepatic macrophages are central to the pathogenesis of chronic liver injury and considered as potential targets for drug discovery. While numerous macrophage-targeting strategies for liver fibrosis intervention currently remain in preclinical development, advancing our comprehension of macrophage plasticity and subset-specific functions holds significant potential. A deeper understanding of macrophage heterogeneity could provide a new therapeutic strategy against liver fibrosis, ultimately improving clinical outcomes for patients with chronic liver diseases.